Tick paralysis in dogs and cats in Australia: treatment and prevention deliverables from 100 years of research. Issue 1 (24th November 2019) - Padula, AM; Leister, EM; Webster, RA
Abstract : This review of tick paralysis caused by Ixodes holocyclus in Australia addresses the question: What are the key discoveries that have enabled effective treatment and prevention of tick paralysis in dogs and cats? Critical examination of 100 years of literature reveals that arguably only three achievements have advanced treatment and prevention of tick paralysis in animals. First, the most significant treatment advance was the commercial availability of tick antiserum in the 1930s. Hyperimmune serum currently remains the only specific anti‐paralysis tick therapy available to veterinarians in Australia. Second, advances in veterinary critical care have increased survival rates of the most severely affected dogs and cats. Critical care advancements have been enabled through specialised veterinary hospitals that can provide appropriate care 24 h a day, and advanced training of veterinarians, veterinary nurses and technicians. Third, perhaps that biggest advance of all in the last 100 years of research has been the commercial availability of the isooxazoline class of acaricidal preventatives in Australia specifically for I. holocyclus . This highly effective class of preventatives offers long duration of action, low cost, spot‐on or oral formulations and a low rate of adverse reactions. Animal owners and veterinarians now have the most useful tool of all – a reliable preventative. This review reveals the key events in research over the last 100 years and the tortuous pathway to delivering better treatment and preventative options for this enigmatic Australian parasite.